Initiation and Termination of Bacterial Deoxyribonucleic Acid Replication in Low Concentrations of Chloramphenicol - Lark, Karl G. (1973)
Escherichia coli 15T(−) can initiate a cycle of deoxyribonucleic acid replication with equal efficiency in the presence of 25 or 50 μg of chloramphenicol/ml. However, these replication cycles are not completed in the presence of these drug concentrations, and the amount of replication decreases with increasing drug concentration.